A Perlocutionary Analysis of Fans’ Resonance in TikTok Comments on Justin Bieber’s Coachella Comeback Performance of Beauty and a Beat - Salwa Naila Humaira; Zaskia Fatimah; Cecilia Novalisa Situmorang; Salsa Aila; Ratu Aliqa Syahkirana Idham; Dian Marisha Putri (Medan Resource Center, 2026)
Justin Bieber's performance of